ADVANTAGES AND PROSPECTS FOR IMPROVEMENT OF THE “STUDY IN UZBEKISTAN” PLATFORM IN ATTRACTING FOREIGN STUDENTS (The Conference Hub, 2025)
This article explores the current advantages and future development prospects of the "Study in Uzbekistan" platform as a tool for attracting international students. The study highlights the platform's role in promoting Uzbek higher education abroad, its user-friendly design, multilingual content, and accessibility. Moreover, it identifies the challenges faced in the areas of digital marketing, academic program visibility, and international recognition. The article proposes practical solutions for enhancing the platform, such as improving SEO strategies, expanding partnerships with foreign institutions, and ensuring regular updates. Ultimately, the study emphasizes the importance of digital innovation and strategic communication in strengthening Uzbekistan’s global educational presence.